Perceived Service Quality Factors Influencing Undergraduate Students’ Satisfaction at Universities in Java and Bali - Bonaventura Darryl Angkatirta; Indra Marhaendra; Ida Bagus Gede Widana Widiatmaka; Kevin Pratama; Tessa Natasha Fitriyanti (Forum Dosen Indonesia, 2020)
The main objective of this research is to study the relationship between tangibility, trustworthiness, response capacity, guarantee, empathy, and innovative learning approach that affect the value of college students’ satisfaction on the islands of Java and Bali. A quantitative study was conducted on students in various universities in Java and Bali, through a survey that was applied to the final sample of 205 students. Data analysis is carried out through structural equation modeling and shows that structures that affect students' satisfaction with the tertiary institutions where they study in the islands of Java and Bali are Guarantee, Tangibility, and Empathy factors. Keywords: Undergraduate Students, Perceived Service Quality, Students’ Satisfaction, Innovative Learning Approach